(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The Italian law 219/2017 has established the priority of patient’s informed consent and of the connected principle of autonomy with regards to medical treatments. However, patient’s autonomy is not without exceptions: in particular, it does not apply to treatments contrary to professional ethics and good clinical-assistance practices. This essay aims to inquire the Italian legal regulation on the female choice among different types of childbirth and delivery methods. Two different cases are examined: the case in which the patient opts for a caesarean section in the absence of any medical indication, and the opposite case in which, instead, the patient opts for a vaginal delivery, even if there are medical indications that would advise against it. For each case I will reconstruct the current legal discipline and, then, I will make some critical considerations on it.